1998
DOI: 10.1126/science.280.5364.734
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Inactivation of MAP-Kinase-Kinase by Anthrax Lethal Factor

Abstract: Anthrax lethal toxin, produced by the bacterium Bacillus anthracis, is the major cause of death in animals infected with anthrax. One component of this toxin, lethal factor (LF), is suspected to be a metalloprotease, but no physiological substrates have been identified. Here it is shown that LF is a protease that cleaves the amino terminus of mitogen-activated protein kinase kinases 1 and 2 (MAPKK1 and MAPKK2) and that this cleavage inactivates MAPKK1 and inhibits the MAPK signal transduction pathway. The iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
748
0
12

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 963 publications
(766 citation statements)
references
References 20 publications
6
748
0
12
Order By: Relevance
“…It involved both B-cell and T-cell zones of lymph nodes and spleen similarly but was also prominent near clusters of bacilli. Lethal toxin interferes with intracellular signaling (23) and may induce apoptosis. Inflammatory response was scant compared with the magnitude of necrosis/apoptosis, but neutrophils were prominent in patients with shorter survival, whereas mononuclear cells (large lymphocytes, immunoblasts, and macrophages) were significantly associated with longer survival.…”
Section: Epidemiological and Clinical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…It involved both B-cell and T-cell zones of lymph nodes and spleen similarly but was also prominent near clusters of bacilli. Lethal toxin interferes with intracellular signaling (23) and may induce apoptosis. Inflammatory response was scant compared with the magnitude of necrosis/apoptosis, but neutrophils were prominent in patients with shorter survival, whereas mononuclear cells (large lymphocytes, immunoblasts, and macrophages) were significantly associated with longer survival.…”
Section: Epidemiological and Clinical Variablesmentioning
confidence: 99%
“…EF acts as an Ca ϩ2 -and calmodulindependent adenylate cyclase which induces edema (22). LF is a metalloprotease that cleaves the amino terminus of MAP kinase kinases 1 and 2 and thus inhibits the intracellular MAPK signal transduction pathway (23), which may favor apoptosis. A sublethal concentration of LF also causes macrophages to produce TNF-␣ and IL-1 (24), which might induce pathologic effects.…”
mentioning
confidence: 99%
“…To determine the activation levels of MAP kinase, we have used Western blots in conjunction with antibodies speci®c for the dual phosphorylated active MAP kinases (p44 ERK1 and p42 ERK2) (Duesbery et al, 1998;Majeti et al, 1998;Yablonski et al, 1998). Densitometric scanning was used to quantitate the activation levels of MAP kinases (active ERK1,2) in relation to the amount of MAP kinase proteins present.…”
Section: Grb2 Protein Inhibition Led To Inactivation Of Map Kinase Inmentioning
confidence: 99%
“…Rabbit antibodies speci®c for MAP kinase and active ERK1,2 proteins were purchased from Oncogene and New England Biolabs, respectively. The latter antibody recognizes only active, but not inactive, ERK1,2 (Duesbery et al, 1998;Majeti et al, 1998;Yablonski et al, 1998). Anti-mouse or anti-rabbit secondary antibodies conjugated with horseradish peroxidase were obtained from Amersham.…”
Section: Antibodiesmentioning
confidence: 99%
“…In this regard, it has been shown that intracellular pathogens such as Yersinia, which infect macrophages, have virulence factors that deactivate macrophages through p38 inhibition, preventing TNF secretion [37]. Bacillus antracis releases the anthrax lethal toxin, a major virulence factor that proteolytically cleaves MKK1 and MKK2, inactivating them and leading to inhibition of the ERK signal transduction pathway in macrophages [38]. Moreover, Leishmania donovani evade the activation of p38, JNK and ERK during infection of naive macrophages [39].…”
Section: Discussionmentioning
confidence: 99%